Back Cover: Crystallin Nanofibrils: A Functionalizable Nanoscaffold with Broad Applications Manufactured from Waste (ChemPlusChem 5/2015). Issue 5 (9th April 2015) - Kaur, Manmeet; Roberts, Sarah; Healy, Jackie; Domigan, Laura; Vasudevamurthy, Madhusudan; Gerrard, Juliet A.; Sasso, Luigi
<x xml:space="preserve">Abstract</x> The back cover picture shows the recycling of crystallin proteins from fish eye lenses, a waste material from the New Zealand fishing industry, to create biological nanofibrils through protein self‐assembly. The bionanofibrils can then be functionalized with several enzymes by a versatile gluteraldehyde cross‐linking approach, turning them into an inexpensive, stable, and reusable bionanoscaffold. Details are given in the Full Paper by Luigi Sasso et al. on page 810.